2004
DOI: 10.1007/s00417-003-0805-7
|View full text |Cite
|
Sign up to set email alerts
|

Delay in diagnosis and outcome of Acanthamoeba keratitis

Abstract: A diagnostic delay of less than 18 days between onset of symptoms and start of anti-amoebic treatment results in a better final VA after medical treatment and obviates the need for urgent and elective penetrating keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 23 publications
5
101
1
4
Order By: Relevance
“…Previous studies have suggested that an earlier time to diagnosis results in more favorable outcomes, [4][5][6]12,13 yet our results suggest symptom duration is not a strong predictor of final visual outcome when compared with corneal disease stage at presentation. Patients presenting with a symptom duration of 3 or more weeks were more likely to have a final visual acuity less than 20/25, but it was not statistically significant in univariate analysis (OR, 2.55; 95% CI, 0.83-7.88).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have suggested that an earlier time to diagnosis results in more favorable outcomes, [4][5][6]12,13 yet our results suggest symptom duration is not a strong predictor of final visual outcome when compared with corneal disease stage at presentation. Patients presenting with a symptom duration of 3 or more weeks were more likely to have a final visual acuity less than 20/25, but it was not statistically significant in univariate analysis (OR, 2.55; 95% CI, 0.83-7.88).…”
Section: Discussioncontrasting
confidence: 69%
“…Although diagnostic and therapeutic advances have significantly improved overall prognosis, recalcitrant infections and poor outcomes persist in some cases. 1,2 Previous reports suggest worse outcomes are associated primarily with later disease presentation, [3][4][5][6] although the most appropriate measure of late disease and confounding variable effects, such as previous medication use, clinical disease characteristics, and diagnostic modalities, have not been identified. The purpose of this study is to identify prognostic factors for disease outcome and visual morbidity through analysis of a recent AK outbreak in the Chicago area.…”
mentioning
confidence: 99%
“…probably got Acanthamoeba infection after trauma to the eye and contaminated water exposure. Diagnosis of Acanthamoeba keratitis infection can be made by identifying trophozoites and cysts in corneal scrapings or by cultures of contact lens disinfectants [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reliable detection of Acanthamoeba is essential for an accurate diagnosis of AK. As delayed diagnosis has been associated with poor visual outcomes (12,13), it is important to identify a method for the rapid and specific diagnosis of AK.…”
mentioning
confidence: 99%